(untitled) (Bangladesh Journal of Anatomy, 2021)
Objectives: This study was aimed to find out the views of students regarding light microscope as a teaching-learning tool in Histology Practical class in undergraduate medical education of Bangladesh. Methods: A cross sectional study was conducted from a period of one year. Data were collected from 1st year students of 10 medical colleges. A semi-structured survey questionnaire having multiple response answers was used for obtaining information from the students. Results: A majority of the students figured out ‘groups of students sharing one microscope’ and ‘difficulty to identify specific structures on slides’ as their most encountered difficulty with microscopes and glass slides respectively. Conclusions: Students facing difficulties with use of light microscope in histology practical sessions. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 2, pp. 28-31